1964
DOI: 10.1021/ja01072a019
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of α-Chymotrypsin Reactions in the Presence of Added Nucleophiles

Abstract: T h e effect of added nucleophiles such as methanol, ethanol, and hydroxylamine on the kinetics of a-chymotrypsincatalyzed reactions is interpreted in terms of the competitive partitioning of the acyl-enzyme intermediate by water and the added nucleophile according to eq. 2. In agreement with this hypothesis, the rate of deacylation of trans-cinnamoyl-a-chymotrypsiri in methanol-water solutions is dependent on the methanol concentration, and the products of the reaction are both methyl cinnamate and cinnamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
1

Year Published

1969
1969
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(59 citation statements)
references
References 3 publications
3
54
1
1
Order By: Relevance
“…an amine compound, a partitioning of the acyl-enzyme may take place to yield a hydrolysis product and an aminolysis product. BENDER et al (13) and FASTREZ and FERSHT (53) found that when methanol, ethanol, glycine amide or alanine amide were added as nucleophiles to chymotrypsin it reacted with ester substrates according to the simple reaction model shown in Scheme 6, in which it is assumed that neither water nor the added nucleophile bind to the enzyme prior to the reaction with the acyl-enzyme intermediate. Hence, the ratio of the two reaction products being formed,…”
Section: Binding Sites For Nucleophilesmentioning
confidence: 99%
“…an amine compound, a partitioning of the acyl-enzyme may take place to yield a hydrolysis product and an aminolysis product. BENDER et al (13) and FASTREZ and FERSHT (53) found that when methanol, ethanol, glycine amide or alanine amide were added as nucleophiles to chymotrypsin it reacted with ester substrates according to the simple reaction model shown in Scheme 6, in which it is assumed that neither water nor the added nucleophile bind to the enzyme prior to the reaction with the acyl-enzyme intermediate. Hence, the ratio of the two reaction products being formed,…”
Section: Binding Sites For Nucleophilesmentioning
confidence: 99%
“…amino compounds, the acylenzyme intermediate will react both with water to give a hydrolysis product and with the amine to give an aminolysis product. BENDER et al ( 1 ) and FASTREZ and FERSHT (9) found that when methanol, ethanol, glycine amide or alanine amide were added as nucleophiles to chymotrypsin it reacted with ester substrates according to the simple reaction model shown in Scheme ~[w] Scheme 1. Competition between water (W) and other nucleophile (N) in the serine protease catalyzed hydrolysis of ester substrates as proposed by BENDER et al (1).…”
Section: Introductionmentioning
confidence: 99%
“…Since DEG influence could be suspected of being nucleophilic, Bender's simplest equation was examined [19]:…”
Section: Discussionmentioning
confidence: 99%